Digital Game As A New Media And Use Of Digital Game In Education - Yengin, Deniz (Iated-Int Assoc Technology Education A& Development, Lauri Volpi 6, Valenica, Burjassot 46100, Spain, 2011)
Transfer of information is trying to stay alive with the language but it is also supported and developed by the discovery of calligraphy. The development of technology in writing, keep records of information systematically. The discovery of electricity was opened in front of the electromagnetic discoveries and sharing of knowledge gained momentum over the channels. According to Huizinga game "game is an activity which is done voluntarily and in regular activities in a particular time and in space". This shows us the concept of the game is not "an unnecessary activity", it has turned into a sense of social and individual vital activity. Reproduced by the codes are real, users in different ways transmitted. Digital game is one of the ways of transmission. Digital media tools such as the game is played the video game and computer game. These environments are considered under the heading of Digital Games. Digital games provide an interactive environment with individuals as they allow electiveness, mobility and non-linearity. In an era of economic angst and where real and virtual identities are being disputed, individuals of the information society are searching for something different other than mass communication. They seek after individual experiences. Digital game environments allow users to gather ideas by allowing them to gain virtual experiences as opposed to real life events. Due to their rich visual content, digital games have the characteristic to shorten the learning period of individuals. Digital games offer users fantasy worlds where they can become lose themselves in different identities. This way through modeling, users are able to 'free' themselves. The main focus in this study will be to analyze the use of digital game in education. Alongside surveys, the study will also make use of literary sources. The universe of the study will be the Turkish students. The data collection method is conducting survey. The answers to the questions in the survey have been transferred to a SPSS environment, where descriptive and inferential analyses will lead us to understand the use of digital game in Turkey's education sector. The relationship between digital games and their users will also be examined. The quantitative study of education with digital games will be a useful source for future studies and will bridge the gap in this area.
Keywords: New Media; Game; Digital Game; Digital Education; Yeni Medya; Oyun; Dijital Oyun; Dijital Eğitim